Molecular Cloning and Optimization for High Level Expression of Cold-Adapted Serine Protease from Antarctic Yeast Glaciozyma antarctica PI12. (30th June 2014) - Alias, Norsyuhada; Ahmad Mazian, Mu'adz; Salleh, Abu Bakar; Basri, Mahiran; Rahman, Raja Noor Zaliha Raja Abd.
Abstract : Psychrophilic basidiomycete yeast, Glaciozyma antarctica strain PI12, was shown to be a protease-producer. Isolation of the PI12 protease gene from genomic and mRNA sequences allowed determination of 19 exons and 18 introns. Full-length cDNA of PI12 protease gene was amplified by rapid amplification of cDNA ends (RACE) strategy with an open reading frame (ORF) of 2892 bp, coded for 963 amino acids. PI12 protease showed low homology with the subtilisin-like protease from fungus Rhodosporidium toruloides (42% identity) and no homology to other psychrophilic proteases. The gene encoding mature PI12 protease was cloned into Pichia pastoris expression vector, pPIC9, and positioned under the induction of methanol-alcohol oxidase ( AOX ) promoter. The recombinant PI12 protease was efficiently secreted into the culture medium driven by the Saccharomyces cerevisiae α -factor signal sequence. The highest protease production (28.3 U/ml) was obtained from P. pastoris GS115 host (GpPro2) at 20°C after 72 hours of postinduction time with 0.5% (v/v) of methanol inducer. The expressed protein was detected by SDS-PAGE and activity staining with a molecular weight of 99 kDa.